Higher topological charge and the QCD vacuum - Fabian Rennecke (Physical Review Research, 2020)
It is shown that gauge field configurations with higher topological charge modify the structure of the QCD vacuum, which is reflected in its dependence on the CP-violating topological phase θ. To explore this, topological susceptibilities and the production of axion dark matter are studied here. The formers characterize the topological charge distribution and are therefore sensitive probes of the topological structure of QCD. The latter depends on the effective potential of axions, which is determined by the θ dependence of QCD. The production of cold dark matter through the vacuum realignment mechanism of axions can, therefore, be affected by higher topological charge effects. This is discussed qualitatively in the deconfined phase at high temperatures, where a description based on a dilute gas of instantons with arbitrary topological charge is valid. As a result, topological susceptibilities exhibit a characteristic temperature dependence due to anharmonic modifications of the θ dependence. Furthermore, multi-instanton effects give rise to a topological mechanism to increase the amount of axion dark matter.